2021
DOI: 10.1589/rika.36.361
|View full text |Cite
|
Sign up to set email alerts
|

Factors of Gait Independence at 15 Days after Stroke Onset and Their Interrelationships in StrokDecision Tree Analysise Patients:

Abstract: The aim of this study was to reveal predictors of gait independence at 15 days after stroke onset using a functional assessment of patients and decision tree analysis at stroke onset. [Participants and Methods] A total of 612 acute stroke patients were enrolled in this study. A total of 26 independent variables were measured at stroke onset: age, gender, disease name, the Stroke Impairment Assessment Set (SIAS), Short Form Berg Balance Scale (SFBBS) total score, Timed Up and Go Test-Reserve (TUG-R), cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…They did not describe the detailed motor function scores of the patients’ upper and lower extremity motor function [ 31 ]. Hiratsuka et al reported the detailed SIAS-MLE scores of patients independently ambulating (an FAC score of 4 or 5) 15 days after stroke onset [ 32 ]. The scores (mean ± standard deviation) were 4.3 ± 1.2, 4.4 ± 1.2, and 4.3 ± 1.0 for the hip-flexion, knee-extension, and foot-pat tests, respectively [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They did not describe the detailed motor function scores of the patients’ upper and lower extremity motor function [ 31 ]. Hiratsuka et al reported the detailed SIAS-MLE scores of patients independently ambulating (an FAC score of 4 or 5) 15 days after stroke onset [ 32 ]. The scores (mean ± standard deviation) were 4.3 ± 1.2, 4.4 ± 1.2, and 4.3 ± 1.0 for the hip-flexion, knee-extension, and foot-pat tests, respectively [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hiratsuka et al reported the detailed SIAS-MLE scores of patients independently ambulating (an FAC score of 4 or 5) 15 days after stroke onset [ 32 ]. The scores (mean ± standard deviation) were 4.3 ± 1.2, 4.4 ± 1.2, and 4.3 ± 1.0 for the hip-flexion, knee-extension, and foot-pat tests, respectively [ 32 ]. Although individual SIAS-MLE scores were not evaluated in our study, the total SIAS-MLE score was similar to that reported by Hiratsuka et al [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously investigated the predictors of gait at 15 days after stroke onset based on functional assessments using decision tree analysis. Our study suggested that the Short-Form Berg Balance Scale (SFBBS), an index of balance function, is the most relevant predictor of gait [12]. However, to our knowledge, none of the previous studies have examined the factors and relationships that affect walking independence, including balance and walking ability, longer than 15 days after stroke onset using decision tree analysis.…”
Section: Introductionmentioning
confidence: 89%
“…We have previously investigated the predictors of gait at 15 days after stroke onset based on functional assessments using decision tree analysis. Our study suggested that the Short-Form Berg Balance Scale (SFBBS), an index of balance function, is the most relevant predictor of gait [12].…”
Section: Introductionmentioning
confidence: 99%